Real-time dynamic multilevel optimization for Demand-side Load management - Duy Long Ha; de Lamotte, F.F.; Quoc Hung Huynh (2007 IEEE International Conference on Industrial Engineering and Engineering Management, 2007)
This paper focuses on Demand-Side load Management applied to residential sector. A multi-scale optimization mechanism for demand-side Load management is proposed. It compose the Agent Management of Energy, it carries out the distribution of the energy of the housing by proposing a dynamical threshold of total energy consumption will be applied to each household. The home automation system integrated in each household plays the role of controlling all the energy consumption in the housing by using service flexibilities, which have the possibilities to be modified and controlled. Thanks to the feedback of the satisfaction of the client by the home automation system, the Agent Management can modify the limit of power consumption of the household again. This mechanism of control takes dynamically into account the comfort of the users and satisfies the constraint from the energy production capabilities. A simulation of 200 housings is also illustrated the performance of this control mechanism.